Palaeoethnobotanical Data from the High Mountainous Early Bronze Age Settlement of Tsaghkasar-1 (Mt. Aragats, Armenia) - Roman Hovsepyan (Ethnobiology Letters, 2011)
Palaeoethnobotanical investigations suggest that at least part of the Early Bronze Age population of Tsaghkasar was settled and practiced agriculture in the high mountainous zone. People there appear to have cultivated hexa‐ and tetraploid wheats (probably bread wheat and emmer) and barley (possibly hulled). Bronze Age agriculture in the Southern Caucasus differs from earlier and later period when cultivation of pulses, oil‐producing plants, and other plants was common. This emphasis on the cultivation and use of certain cereal grains at Early Bronze sites such as Tsaghkasar can tentatively be added to a constellation of practices associated with the Kura‐Araxes culture in the South Caucasus.